Full-biodegradable urea coating agent and preparation method thereof

By using a polyurethane coated agent prepared by carbon dioxide -based polyol and biological base materials, the problem of white pollution caused by non -degradation of coated agents in the existing technology, and realized the slow -release urea fertilizer selected by the selected period of efficient biological degradation and the selection of various release periods Essence

CN119371258AActive Publication Date: 2025-01-28CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411521117.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing sustained-release urea coating agents are non-degradable, resulting in 'white pollution' in the soil. The coating process is complex and organic solvents are needed to pollute the environment.

Method used

The polyurethane system prepared by carbon dioxide alcohol and biological base materials is obtained by heating and cooling through nitrogen protection and cooling. The coatings and wetting agents are added. After stirring, it is cooled to obtain a full biodegradable coated agent.

Benefits of technology

A complete biological degradation of the coating agent is achieved, the degradation rate exceeds 93%, solving the white pollution caused by non -degraded non -degradation, and the preparation of mitigated urea fertilizers has three choices: 60, 90 days, and 120 days.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108064790000081
    Figure BDA0005108064790000081
Patent Text Reader

Abstract

The invention discloses a full-biodegradable urea coating agent and a preparation method thereof.According to the full-biodegradable urea coating agent and the preparation method thereof, a polyurethane system is prepared from carbon dioxide-based polyol and a bio-based material, the obtained coating agent can be completely biodegraded, the degradation rate exceeds 93%, and white pollution caused by non-degradability of a traditional slow-release urea coating agent is solved; the slow-release urea fertilizer is an environment-friendly coating agent, and the slow-release urea fertilizer with three different release periods of 60 days, 90 days and 120 days can be prepared according to different internal cross-linked structures in the coating agent structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slow-release fertilizers, and in particular relates to a fully biodegradable urea coating agent and a preparation method thereof. Background Art

[0002] According to the results of the investigation by the Food and Agriculture Organization of the United Nations, the average yield increase effect of chemical fertilizers is as high as 40-60%. Nitrogen, phosphorus and potassium fertilizers are the three basic fertilizers, among which nitrogen fertilizer is used in the largest amount. This is because the nitrogen fertility in the soil is not high and nitrogen is not easy to bond in the soil. Urea is an important high-nitrogen fertilizer, also known as carbonic acid amide, with a nitrogen content of up to 46%. It is a neutral fertilizer suitable for any soil. After fertilizing it, the amide bond in its structure must be converted into ammonium nitrogen by the action of microorganisms in the soil before it can be absorbed by the roots of the fabric, which takes 3-5 days. However, urea has a strong hygroscopicity. Once the soil is humid or it rains, it will quickly enter the deep soil layer and leave the absorption range of the fabric roots, causing losses. Moreover, during transportation and storage, water absorption will also lead to nitrogen loss and environmental pollution. In order to solve this problem, many slow-release urea technologies have been developed in recent years, which improve the utilization rate of urea by applying a coating agent on the surface of urea. Coating agents include two categories: inorganic coating agents and organic polymer coating agents. Inorganic coating agents include phosphate rock powder, sulfur, talcum powder, etc. Organic polymer coating agents include two categories of coating sustained-release materials: thermosetting and thermoplastic resins.

[0003] Patent 200410012251.8 reports ammonium sulfate coated urea granular fertilizer and preparation method. The product is in granular form, consisting of a core and a coating. The core is urea, the coating agent is ammonium sulfate, and the weight ratio of ammonium sulfate to urea is 1-4:9-6. After ammonium sulfate coating, the defect of urea losing nitrogen due to moisture absorption and decomposition during storage and transportation can be effectively prevented. The particle size of the urea core is 0.8-2.5 mm, and the thickness of the ammonium sulfate coating is not more than 0.5 mm. The ammonium sulfate solution is sprayed on the surface of urea, and after cooling and drying, urea granules containing the coating agent are obtained, which improves the nutrient utilization rate of urea fertilizer by 2-4%. However, ammonium sulfate as a coating agent is an inorganic coating agent, and its disadvantages are that it has no strength and cannot protect urea granules. In addition, ammonium sulfate is water-soluble, so it will still dissolve in water quickly, resulting in a decrease in urea fertilizer efficiency. Sulfur-coated urea is the first industrial product. The preheated urea is fed into a horizontally rotating cylindrical drum, and the sulfur is heated to 156°C to become molten, and then sprayed onto the surface of urea particles to make it quickly solidify on the surface of urea to obtain sulfur-coated urea. However, this method requires high energy consumption, and the sulfur coating is easily oxidized and broken, and has poor wear resistance. It is easy to break and fall off during storage and transportation, and cracks are generated on the surface. The voids generated during the coating process and the degradation ability of microorganisms on the coating film are reduced. A certain amount of paraffin needs to be sprayed for sealing, which requires multiple processes such as waxing and coating, and increases costs. In addition, a large amount of sulfur is decomposed by microorganisms in the soil, which will lead to soil acidification and damage the soil structure. The common problem of inorganic coating agents is that after crystallization, large-area cracks and holes are formed, which accelerates the release of fertilizer nutrients. Polymer coating agents are widely used in coating materials, including polyethylene, polystyrene, and polyester, because they are not easily decomposed by microorganisms and have good film-forming properties. Li et al. (Wuhan Univ Technol, 2012, 27: 126-129) used isocyanate and polyol to form a dense polyurethane coating layer with a thickness of 10 to 15 microns on the surface of urea particles, and added plasticizer paraffin during the reaction to increase the fluidity of the reactants, so as to form an ultra-thin coating layer. Nutrient experiments showed that the urea sustained release time was 40 to 50 days. The advantages of polymer coating agents are that the coating layer has good adhesion to urea particles and can form a wear-resistant coating. The fertilizer nutrient release rate is controlled by polymer composition and film thickness. The problems with this technology are that the coating process is complicated, organic solvents are required, solvents pollute the environment, and they are not degradable. The common problem of the above technical solutions is that the coating agent cannot be degraded in the soil. Although the utilization rate of urea is improved, these coating agents will bring "white pollution" problems to the soil.

[0004] Invention patent 201611022848.X reports a biodegradable fertilizer slow-release coating, which is a two-component A and B, wherein component A is a solvent-free alkyd resin with a relative molecular weight of 600-1200; component B is a diisocyanate curing agent, which can extend the release time of the fertilizer by about 40 times. Invention patent 200710013099.9 discloses a type of biodegradable self-controlled slow-release fertilizer and its preparation method, a solution-type slow-release material with cellulose, epoxy resin, polyvinyl alcohol and other polymers as the main body. However, the above two coating materials have poor degradation performance, especially epoxy resin, polyvinyl alcohol, and alkyd resin have very poor degradation performance. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a fully biodegradable coating agent.

[0008] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a fully biodegradable coating agent, characterized in that: comprising:

[0009] Under nitrogen protection, the pre-dehydrated carbon dioxide-based diol, diisocyanate, catalyst, small molecule polyol and bio-based diol are mixed uniformly, heated for 1.5 to 2 hours, and then cooled to room temperature to obtain a coating agent resin;

[0010] The coating resin temperature is controlled at 30-45° C., and then a pigment, a wetting agent, a leveling agent, a dispersant and a wax are added, stirred for 30-45 minutes, and cooled to room temperature to obtain the fully biodegradable coating agent.

[0011] As a preferred embodiment of the preparation method of the present invention, the water content of the carbon dioxide-based diol is treated to be within 300 ppm, the molecular weight is 500 to 3000, and the carbonate content is 15 to 50%.

[0012] As a preferred embodiment of the preparation method of the present invention, the diisocyanate is a mixture of one or more of isophorone diisocyanate, 1,6-hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, xylylene diisocyanate, 1,4-cyclohexane diisocyanate, tetramethyl meta-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexane dimethyl diisocyanate or norbornane diisocyanate.

[0013] As a preferred embodiment of the preparation method of the present invention, the small molecule polyol is a polyol having a hydroxyl functionality of not less than 3, preferably a mixture of one or more of glycerol, trimethylolpropane, pentaerythritol, and dipentaerythritol; the bio-based diol is a mixture of one or more of isosorbide, castor oil, cellulose, lignin, rosin, palm oil, modified cashew nut shell oil polyol, rapeseed oil, and soybean oil.

[0014] As a preferred embodiment of the preparation method of the present invention, the mass ratio of the carbon dioxide-based diol, diisocyanate, catalyst, small molecule polyol and bio-based diol is 2103.5-6250.2: 336.4-998.5: 0.75-3.9: 40.5-164.3: 59.3-726.5.

[0015] As a preferred embodiment of the preparation method of the present invention, the pigment is one of iron oxide red S130, iron oxide green 5605, iron oxide yellow 313 and iron oxide blue YHT-01; the wetting agent is one or more of BYK-331, BYK-333, BYK-378, BYK-310, BYK-337, BYK-320 and BYK-306; the leveling agent is BYK-356, BYK-358N, BYK-355, BYK-356N ... The dispersant is one or more of BYK-9076, DISPERBYK-161, DISPERBYK-163, DISPERBYK-2000, DISPERBYK-2020 and DISPERBYK-2025; the paraffin is one or more of semi-refined paraffin No. 56, semi-refined paraffin No. 58 and semi-refined paraffin No. 60.

[0016] As a preferred embodiment of the preparation method of the present invention, the mass ratio of the pigment, wetting agent, leveling agent, dispersant and wax is 35.1-226.4: 10.5-56.2: 16.2-40.1: 18.4-75.8: 20.1-135.8.

[0017] As a preferred embodiment of the preparation method of the present invention, the heating is performed for 1.5 to 2 hours, wherein the heating temperature is 85 to 95°C.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide a fully biodegradable coating agent for use in the preparation of fully biodegradable slow-release urea.

[0019] As a preferred embodiment of the application of the present invention, the preparation method of the fully biodegradable slow-release urea includes heating urea particles with an average particle size of 3.0 to 5 mm to 80°C for 15 minutes, then adding a coating agent, heating to 90 to 100°C, adjusting the rotation speed to 50 r / min, adding 20 g of a cross-linking agent after 15 minutes, continuing to stir for 20 minutes, lowering the temperature to room temperature, discharging, and obtaining slow-release urea.

[0020] Beneficial effects of the present invention:

[0021] The present invention uses a polyurethane system prepared from carbon dioxide-based polyol and bio-based materials. The obtained coating agent is completely biodegradable with a degradation rate of more than 93%, which solves the white pollution caused by the non-degradability of traditional slow-release urea coating agents. It is an environmentally friendly coating agent, and according to the different internal cross-linking structures in the coating agent structure, slow-release urea fertilizers with three different release periods of 60 days, 90 days and 120 days can be prepared. DETAILED DESCRIPTION

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0024] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0025] Raw materials used in the present invention:

[0026] Isophorone diisocyanate, diphenylmethane-4,4'-diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, glycerol, isosorbide, palm oil, pentaerythritol, rapeseed oil, dipentaerythritol, and soybean oil were from MacLean Reagents. BYK-310, BYK-331, BYK-337, BYK-340, BYK-355, BYK-356, BYK-9076, BYK-306, BYK-392, DISPERBYK-163, DISPERBYK-2000, and DISPERBYK-2025 were from BYK. Polymethylene polyphenyl isocyanate PM200 was from Yantai Wanhua Group. Semi-refined paraffin wax No. 56, No. 60 and No. 58 were from Daqing Petrochemical Company of PetroChina Co., Ltd. Iron oxide red S130, iron oxide blue S463, iron oxide yellow S313 and iron oxide green S5605 were from Yipin Pigment Co., Ltd. Urea was from Shandong Hualu Hengsheng Group Co., Ltd.

[0027] Example 1

[0028] This embodiment is a preparation of a fully biodegradable coating agent, comprising the following steps:

[0029] (1) Under nitrogen protection, 6250.2 g of pre-dehydrated carbon dioxide-based diol (prepared in Example 8 of Invention Patent 201210086834.X, with a molecular weight of 2300 g / mol and a carbonate content of 41%), 998.5 g of isophorone diisocyanate, 3.5 g of dibutyltin dilaurate, 55.2 g of glycerol and 175.3 g of isosorbide were added to a three-necked flask, the temperature was controlled at 85° C., and the reaction was carried out for 2 hours. The mixture was cooled to room temperature to obtain a coating agent resin.

[0030] (2) The temperature of the obtained coating resin was controlled at 30° C., and then 83.5 g of iron oxide red S130, 16.8 g of BYK-331, 21.5 g of BYK-356, 30.4 g of BYK-9076 and 40.1 g of No. 56 semi-refined paraffin were added, stirred for 30 min, and cooled to room temperature to obtain a coating agent.

[0031] Example 2

[0032] This embodiment is a preparation of a fully biodegradable coating agent, comprising the following steps:

[0033] (1) Under nitrogen protection, 3620.5 g of pre-dehydrated carbon dioxide-based diol (prepared in Example 7 of Invention Patent 201210086834.X, with a molecular weight of 3000 g / mol and a carbonate content of 40.6%), 336.4 g of 1,6-hexamethylene diisocyanate, 1.8 g of stannous octoate, 40.5 g of trimethylolpropane and 726.5 g of castor oil were added to a three-necked flask, the temperature was controlled at 95° C., and the reaction was carried out for 1.5 hours. The mixture was cooled to room temperature to obtain a coating agent resin.

[0034] (2) The temperature of the obtained coating resin was controlled at 45° C., and then 351 g of iron oxide green 5605, 56.2 g of BYK-333, 40.1 g of BYK-358N, 75.8 g of DISPERBYK-161 and 135.8 g of No. 58 semi-refined paraffin were added, stirred for 45 min, and cooled to room temperature to obtain a coating agent.

[0035] Example 3

[0036] This embodiment is a preparation of a fully biodegradable coating agent, comprising the following steps:

[0037] (1) Under nitrogen protection, 2485.2 g of pre-dehydrated carbon dioxide-based diol (prepared in Example 9 of Invention Patent 201210086834.X, with a molecular weight of 2000 g / mol and a carbonate content of 43.8%), 839.4 g of 4,4'-dicyclohexylmethane diisocyanate, 2.6 g of bismuth neodecanoate, 164.3 g of glycerol and 324.1 g of palm oil were added to a three-necked flask, the temperature was controlled at 90°C, and the reaction was carried out for 1 hour. The mixture was cooled to room temperature to obtain a coating agent resin.

[0038] (2) The temperature of the obtained coating resin was controlled at 35° C., and then 81.5 g of iron oxide blue YHT-01, 26.5 g of BYK-310, 18.2 g of BYK-355, 30.2 g of DISPERBYK-163 and 48.1 g of No. 60 semi-refined paraffin were added, stirred for 32 min, and cooled to room temperature to obtain a coating agent.

[0039] Example 4

[0040] This embodiment is a preparation of a fully biodegradable coating agent, comprising the following steps:

[0041] (1) Under nitrogen protection, 2240.5 g of pre-dehydrated carbon dioxide-based diol (prepared in Example 12 of Invention Patent 201210086834.X, with a molecular weight of 1600 g / mol and a carbonate content of 63.2%), 398.5 g of 1,4-cyclohexane diisocyanate, 3.9 g of stannous octoate, 68.5 g of pentaerythritol and 148.2 g of rapeseed oil were added to a three-necked flask, the temperature was controlled at 88° C., and the reaction was carried out for 2 hours. The mixture was cooled to room temperature to obtain a coating agent resin.

[0042] (2) The temperature of the obtained coating resin was controlled at 30-45° C., and then 40.8 g of yellow iron oxide 313, 10.5 g of BYK-337, 16.2 g of BYK-340, 18.4 g of DISPERBYK-2000 and 20.1 g of No. 58 semi-refined paraffin were added, stirred for 45 min, and cooled to room temperature to obtain a coating agent.

[0043] Example 5

[0044] This embodiment is a preparation of a fully biodegradable coating agent, comprising the following steps:

[0045] (1) Under nitrogen protection, 2103.5 g of pre-dehydrated carbon dioxide-based diol (Example 11 in Invention Patent 201210086834.X, molecular weight 1500 g / mol, carbonate content 78.6%), 420.1 g of isophorone diisocyanate, 1.3 g of dibutyltin dilaurate, 50.8 g of dipentaerythritol and 130.5 g of soybean oil were added to a three-necked flask, the temperature was controlled at 92° C., and the reaction was carried out for 1.5 hours. The mixture was cooled to room temperature to obtain a coating agent resin.

[0046] (2) The temperature of the obtained coating resin was controlled at 30-45° C., and then 130.5 g of iron oxide green 5605, 40.5 g of BYK-310, 20.6 g of BYK-355, 24.1 g of DISPERBYK-2020 and 48.6 g of No. 60 semi-refined paraffin were added, stirred for 35 min, and cooled to room temperature to obtain a coating agent.

[0047] Example 6

[0048] This embodiment is a preparation of a fully biodegradable coating agent, comprising the following steps:

[0049] (1) Under nitrogen protection, 2858.4 g of pre-dehydrated carbon dioxide-based diol (prepared in Example 10 of Invention Patent 201210086834.X, with a molecular weight of 2100 g / mol and a carbonate content of 50%), 446.3 g of 1,4-cyclohexanedimethyl diisocyanate, 0.75 g of bismuth neodecanoate, 101.3 g of glycerol and 59.3 g of palm oil were added to a three-necked flask, the temperature was controlled at 85° C., and the reaction was carried out for 1.5 hours. The mixture was cooled to room temperature to obtain a coating agent resin.

[0050] (2) The temperature of the obtained coating resin was controlled at 40° C., and then 226.4 g of iron oxide red S130, 24.7 g of BYK-306, 18.5 g of BYK-392, 29.6 g of DISPERBYK-2025 and 85.3 g of No. 56 semi-refined paraffin were added, stirred for 45 minutes, and cooled to room temperature to obtain a coating agent.

[0051] Example 7

[0052] The difference between this embodiment and embodiment 5 is that the dipentaerythritol in step (1) is replaced by glycerol, and the remaining steps are the same as those in embodiment 5.

[0053] Example 8

[0054] The difference between this embodiment and embodiment 5 is that the isophorone diisocyanate in step (1) is replaced by diphenylmethane-4,4'-diisocyanate, and the remaining steps are the same as those in embodiment 5.

[0055] Comparative Example 1

[0056] The difference between this comparative example and Example 5 is that the carbon dioxide-based diol (Example 11, molecular weight of 1500 g / mol, carbonate content of 78.6%) in step (1) is replaced by butanediol adipate (molecular weight of 1500 g / mol), and the remaining steps are the same as Example 5.

[0057] Comparative Example 2

[0058] The difference between this comparative example and Example 5 is that the carbon dioxide-based diol (Example 11, molecular weight of 1500 g / mol, carbonate content of 78.6%) in step (1) is replaced by polypropylene glycol (molecular weight of 1500 g / mol), and the remaining steps are the same as Example 5.

[0059] Example 9

[0060] This embodiment is a preparation of a fully biodegradable slow-release urea, comprising the following steps:

[0061] 1000 g of urea granules with an average particle size of 3.0-5.0 mm were added to a 3L drum and preheated to 80° C. for 15 min. Then, 15 g of the coating agent of Examples 1-8 and Comparative Examples 1-2 were added to the urea granules. At the same time, the fertilizer in the drum was heated to 90-100° C. The speed was adjusted to 50 rpm. After 15 min, 10 g of polyisocyanate PAPI was added and stirring was continued for 20 min. The temperature was lowered to room temperature and the material was discharged to obtain slow-release controlled urea, which were marked as N1-N8 and D1-D2, respectively.

[0062] Example 10

[0063] This example is to perform a performance test on the fully biodegradable slow-release urea prepared in Example 9, comprising the following steps:

[0064] (1) Initial nutrient release rate: The mass fraction of nitrogen released after immersing the prepared urea slow-release fertilizer in static water at 25°C for 24 hours to the total nitrogen.

[0065] (2) Cumulative nutrient release rate: The mass fraction of the total nitrogen released by urea slow-release fertilizer in still water at 25°C over a certain period of time

[0066] (3) Nutrient release period: The time required for urea slow-release fertilizer to reach 80% of the cumulative nutrient release rate in still water at 25°C.

[0067] (4) Biodegradation test: According to GB / T19277.1-2011, the biodegradability of the coating agent was tested to study its final aerobic biodegradability and disintegration ability under controlled composting conditions. In a 2L test system, the coating agent was used as an organic carbon source, and the test mixture was aerated at a controlled rate with carbon dioxide-free air. The degradation rate was determined by measuring the amount of carbon dioxide produced. 240g of culture soil was mixed with 40g of the coating agent obtained by the present invention and 40g of microcrystalline cellulose, and 240g of culture soil was used as a blank control. Distilled water was added to adjust the humidity of the mixture to about 50%. The compost container was placed in a test environment at (58±2)℃, and the test system was aerated with CO2-free humidified air at a flow rate of 0.05L / min, and the test was carried out under (58±2)℃. The ratio of the amount of carbon dioxide actually produced by the test material during the test to the theoretical release of carbon dioxide of the test material was used as the biodegradation rate of the test material.

[0068] The test results of N1~N8 and D1~D2 are shown in Table 1.

[0069] Table 1 N1~N8, D1~D2 performance test results

[0070]

[0071] From the results of the table, it can be seen that the cumulative nutrient release of Example 1, Example 2, Example 3 and Example 6 in 90 days reached 100%, and the release rate in 60 days was 72%, 68%, 74% and 75%, respectively, all within 80%, indicating that the nutrient release period of the urea coated by the coating agent of these three examples is 60 days; the nutrient release of the slow-release urea prepared by the coating of Example 2 and Example 4 was 78% and 73% in 90 days, and reached 80% in 120 days, indicating that the release period of the urea coating agent obtained by Example 2 and Example 4 is 90 days; the nutrient release of the urea slow-release fertilizer obtained by Example 5 in 120 days is 76%, which is lower than 80%, so the release period of the coating agent prepared by this example is 120 days. The reason why the slow-release urea prepared by different coating agents has different release periods is that the small molecule polyols in the coating agent are different. The coating agent structure for a 90-day release period uses trifunctional trimethylolpropane and tetrafunctional pentaerythritol. The high cross-linked network structure increases the cross-linking density of the coating film, thereby increasing the release period of urea. The 120-day release period uses dipentaerythritol with six functionalities, which forms a higher cross-linking density on the urea surface, thereby achieving a longer release period of 120 days. Compared with Example 5, Example 7 uses glycerol with a functionality of 3 to replace dipentaerythritol with a functionality of 6, which reduces the crosslinking density of the coating agent, thereby reducing the compactness of the coating agent, resulting in a faster nutrient release rate, so that the release can reach 90 days, but cannot meet the release of 120 days; Example 8 uses aromatic diisocyanate diphenylmethane-4,4'-diisocyanate to replace isophorone diisocyanate. Since the addition of benzene rings strengthens the rigidity of the coating film, the sustained release effect is improved, so the release of 120 days can still be achieved, and the nutrient release rates of 120 days and 90 days are lower. However, due to the introduction of benzene rings in the coating resin, the biodegradability is reduced. Compared with Example 5, the initial release rate of Comparative Example 1 exceeds the standard requirement of 15%, up to 18%, and the 60-day release period also exceeds the standard requirement of 85%. This is because polybutylene adipate glycol is a polyester with poor water resistance, and the polyol is an aliphatic polyester, so it has certain biodegradability. Compared with Example 5, the initial hair care release, 60-day and 90-day release rates of Comparative Example 2 all meet the standard requirements. This is because polypropylene glycol has certain water resistance and hydrolysis resistance, and thus has a good sustained-release effect. However, polypropylene glycol is a polyether and has poor biodegradability.

[0072] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a fully biodegradable coating agent, characterized in that: include, Under nitrogen protection, the pre-dehydrated carbon dioxide-based diol, diisocyanate, catalyst, small molecule polyol and bio-based diol are mixed uniformly, heated for 1.5 to 2 hours, and then cooled to room temperature to obtain a coating agent resin; The coating resin temperature is controlled at 30-45° C., and then a pigment, a wetting agent, a leveling agent, a dispersant and a wax are added, stirred for 30-45 minutes, and cooled to room temperature to obtain the fully biodegradable coating agent.

2. The preparation method according to claim 1, characterized in that: The water content of the carbon dioxide-based diol is processed to be within 300 ppm, the molecular weight is 500-3000, and the carbonate content is 15-50%.

3. The preparation method according to claim 1, characterized in that: The diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, xylylene diisocyanate, 1,4-cyclohexane diisocyanate, tetramethyl meta-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexane dimethyl diisocyanate or a mixture of norbornane diisocyanate.

4. The preparation method according to claim 1, characterized in that: The small molecule polyol is a polyol having a hydroxyl functionality of not less than 3, preferably a mixture of one or more of glycerol, trimethylolpropane, pentaerythritol, and dipentaerythritol; the bio-based diol is a mixture of one or more of isosorbide, castor oil, cellulose, lignin, rosin, palm oil, modified cashew nut shell oil polyol, rapeseed oil, and soybean oil.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon dioxide-based diol, diisocyanate, catalyst, small molecule polyol and bio-based diol is 2103.5-6250.2: 336.4-998.5: 0.75-3.9: 40.5-164.3: 59.3-726.

5.

6. The preparation method according to claim 1, characterized in that: The pigment is one of iron oxide red S130, iron oxide green 5605, iron oxide yellow 313 and iron oxide blue YHT-01; the wetting agent is one or more of BYK-331, BYK-333, BYK-378, BYK-310, BYK-337, BYK-320 and BYK-306; the leveling agent is BYK-356, BYK-358N, BYK-355, BYK-340, BYK-3 22. One or more of BYK-392 and BYK-323. The dispersant is one or more of BYK-9076, DISPERBYK-161, DISPERBYK-163, DISPERBYK-2000, DISPERBYK-2020 and DISPERBYK-2025. The paraffin is one or more of semi-refined paraffin No. 56, semi-refined paraffin No. 58 and semi-refined paraffin No.

60.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the pigment, the wetting agent, the leveling agent, the dispersant and the wax is 35.1-226.4: 10.5-56.2: 16.2-40.1: 18.4-75.8: 20.1-135.

8.

8. The preparation method according to claim 1, characterized in that: The heating is performed for 1.5 to 2 hours, wherein the heating temperature is 85 to 95°C.

9. Use of a fully biodegradable coating agent in the preparation of fully biodegradable slow-release urea, characterized in that: The fully biodegradable coating agent is prepared by the preparation method according to any one of claims 1 to 8.

10. The use according to claim 9, characterized in that: The preparation method of the fully biodegradable slow-release urea comprises the following steps: heating urea particles with an average particle size of 3.0 to 5 mm to 80° C. for 15 minutes, then adding a coating agent, heating to 90 to 100° C., adjusting the rotation speed to 50 r / min, adding 20 g of a cross-linking agent after 15 minutes, continuing to stir for 20 minutes, lowering the temperature to room temperature, discharging the material, and obtaining the slow-release urea.

Citation Information

Patent Citations

  • Biological biodegradable self-control slow-releasing fertilizer and preparation method thereof

    CN101037368A

  • Preparing method of poly (carbonic ester-ether) polyalcohol

    CN102617844B

  • Degradable chemical fertilizer sustained-release coating and preparation method of degradable chemical fertilizer sustained-release coating

    CN106699336A

  • Ammonium sulphate coated urea granule fertilizer and method for preparing same

    CN1241880C

  • Preparing method of poly (carbonic ester-ether) polyalcohol

    CN102617844A

Cited By

  • Carbon dioxide-based low-carbon degradable coated controlled-release fertilizer and preparation method thereof

    CN120117936A

  • Environment-friendly sustained and controlled release fertilizer coating agent as well as preparation method and application thereof

    CN121293051A